2013
DOI: 10.1097/icl.0b013e318281ae06
|View full text |Cite
|
Sign up to set email alerts
|

Physical Entrapment of Hyaluronic Acid During Synthesis Results in Extended Release From Model Hydrogel and Silicone Hydrogel Contact Lens Materials

Abstract: Hyaluronic acid physically incorporated into contact lens materials during synthesis may therefore be released for extended periods of time of up to 7 weeks. Hyaluronic acid release leads to decreased protein adsorption in general. This method has potential for modification of conventional and silicone hydrogel lenses with releasable HA as a wetting agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…Hyaluronic acid (HA), a hydrophilic glycosaminoglycan found throughout the human body, has been used in contact lens rewetting drops and in a range of artificial tear products to treat mild, moderate, and severe dry eye, 155,156 and has been used as a novel internal wetting agent for contact lens materials. [157][158][159][160][161][162] However, to our knowledge, HA has not been shown in any clinical studies to directly improve comfort associated with contact lens wear.…”
Section: Wetting Agent Incorporationmentioning
confidence: 99%
“…Hyaluronic acid (HA), a hydrophilic glycosaminoglycan found throughout the human body, has been used in contact lens rewetting drops and in a range of artificial tear products to treat mild, moderate, and severe dry eye, 155,156 and has been used as a novel internal wetting agent for contact lens materials. [157][158][159][160][161][162] However, to our knowledge, HA has not been shown in any clinical studies to directly improve comfort associated with contact lens wear.…”
Section: Wetting Agent Incorporationmentioning
confidence: 99%
“…In these experiments, it was also shown that the released hyaluronic acid induced a decrease in lysozyme sorption of contact lenses. 28 Eye & Contact Lens Volume 0, Number 0, Month 2015 Dry Eye Treatment by Contact Lens Drug Delivery…”
Section: Rewetting or Comfort Agentsmentioning
confidence: 99%
“…27 Additionally, hyaluronic acid has been physically incorporated into the conventional and silicone hydrogel contact lens material during contact lens synthesis. 28 Hyaluronic acid could be released from p-HEMA hydrogels for at least 21 days and from the silicone hydrogels for an extended period of up to 7 weeks. In these experiments, it was also shown that the released hyaluronic acid induced a decrease in lysozyme sorption of contact lenses.…”
Section: Rewetting or Comfort Agentsmentioning
confidence: 99%
“…Recently, Van Beek and Andrea Weeks co-workers reported hyaluronic acid (HA) containing silicone hydrogels and poly (2-HEMA) gels with HA immobilized as a wetting agent. [15,16] HA has been widely studied since last 20 years as an ophthalmic comfort enhancing agent. [17][18][19] It has been shown to promote water retentive properties and its viscoelasticity provides tear fluid stability in dry eyes.…”
Section: Introductionmentioning
confidence: 99%